Creepy Crayon! - Reynolds, Aaron, 1970-; Brown, Peter, 1979- (New York : Simon & Schuster Books for Young Readers, 2022)
"When Jasper Rabbit finds a purple crayon willing to do his schoolwork for him, he is elated--at first"--.
new kids book 2022 summer.
Ages 4-8.
Grades K-1.
Keywords: Rabbits -- Fiction; Crayons -- Fiction; Imagination & Play